Multiple microcrystal deposition disease in a patient with systemic lupus erythematosus. Issue 3 (June 1984) - Rodríguez, M A; Paul, H; Abadí, I; Bravo, J R; Armas, P
Abstract : A 17-year-old female patient with systemic lupus erythematosus (SLE) developed chronic tophaceous gout, chondrocalcinosis and articular capsule calcification in several joints. Analysis of synovial fluid and tophi revealed the coexistence of monosodium urate, calcium pyrophosphate, hydroxyapatite, and cholesterol crystals.